Collecting bullying and cyber aggression data with schools in the digital age: Opportunities and challenges of the online approach - Mc Guckin, Conor (SAGE, 2017)
In this case study, the research methods used to collect data from school-based populations online, by postal survey and in a face-to-face setting are examined. While the online context provides a great opportunity for data collection with relative ease, it also presents a number of challenges for researchers. Online data collection offers the unique potential for large national and international sampling, at minimal cost, and can allow for access to groups which are typically under-represented in research studies. However, there are also difficulties associated with this approach such as the potential for bias and difficulties in obtaining a high response rate. Furthermore, although there is often greater cost associated with face-to-face data collection at a national level, there are potential benefits such as consistent administration of research instruments and meaningful contact with the population of interest. The review of the methods used in our research will highlight some of the key factors associated with conducting research with schools in the digital age.
SAGE Research Methods Cases.
Keywords: Inclusive Society; ANTI-BULLYING POLICY; BULLY; BULLY-VICTIM; BULLY/VICTIM PROBLEMS; BULLYING; Bullying; Bullying; Bullying, Harassment and Violence in School & the Workplace; Cyberbullying; EDUCATION; School Bullying; Traditional Bullying; prevention of bullying; Children; Education; Youth